RADIOGENIC ISOTOPES IN FLUID INCLUSIONS - Villa I.M. (My University, 2001)
Radiogenic isotopes studied in fluid inclusions are still a limited field, with great potential for expansion as analytical techniques improve. The main limitation for Sr, Ar and He isotope work is the very small number of radiogenic atoms produced in a typical fluid inclusion. The requirements to analysts are correspondingly high. Examples show that isotopic tracing on fluid inclusion fluids can be a decisive tool in solving geological problems.
Keywords: FLUID INCLUSIONS; AR ISOTOPES; HE ISOTOPES; SR ISOTOPES